Effect analysis of the different channel length and depth of photovoltaic thermal system with ∇-groove collector - Saprizal Hadisaputra; Muhammad Zohri; Bahtiar Bahtiar; Ahmad Fudholi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The converted Solar energy as electrical and thermal energy was named photovoltaic thermal (PVT). The aim of this study is to the analysis of different length and depth channel effect of photovoltaic thermal with ∇-groove collector by a mathematical model. The matrix inversion was used to analyze the energy balance equation. Simulation results were conducted below the solar intensity of 800 W/m2 and mass flow rate between 0.0069 kg/s and 0.0491 kg/s. Electrical and thermal efficiency was done to assess the effect of different length and channel depth of PVT system with ∇-groove collector. The effect of different length and depth of ∇-groove collector for electrical and thermal performance is caused by changed mass flow rate. The effect Increasing of the mass flow rate of collector increased the thermal and electrical performance of the ∇-groove collector.